(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2019)
The present study is to assess the significance of weight of fused hyoid bone as a useful metrical index in determination of sex of an individual. The material used in the present study includes 55 fused hyoid bones of known sex of North Indian population, obtained from the cadavers brought to mortuaries for post-mortem. The bone was weighed with the help of electronic weighing scale and the readings were tabulated and statistically calculated. It was noticed that weight of hyoid bone was statistically significant and greater in males than in females. Weight of completely fused hyoid bone showed significant statistical result and can be considered helpful along with other parameters for determination of sex of an unknown hyoid bone.